Curricular offerings in the professional preparation program in health education of the ten selected teacher-education institutions in Manila - Ansaldo, Eleanor Fabella 1939-
The purpose of this study is to find out how the teacher-education institutions in Manila have provided for the health education competencies of teachers in the elementary school. It sought to identify the skills, knowledge and attitudes that have been found necessary for elementary teachers to function effectively in the school health program, to determine the provisions in the curriculum of the studied institutions that are designed to develop the needed competencies in health education in elementary school, and to find out the qualifications of teacher-educators in these institutions in handling health education courses.